Energy transfer and exciton dynamics in photosynthetic pigment–protein complexes - Kell, Adam (Kansas State University, 2016)
The structure-function relationships of natural pigment–protein complexes are of great interest, as the electronic properties of the pigments are tuned by the protein environment to achieve high quantum yields and photon utilization. Determination of electronic structure and exciton dynamics in protein complexes is complicated by static disorder and uncertainties in the properties of system-bath coupling. The latter is described by the phonon profile (or spectral density), whose shape can only be reliably measured experimentally for the lowest energy state. Low-temperature, laser-based spectroscopies are applied towards model pigment–protein complexes, i.e., the Fenna-Matthews-Olson (FMO) and water-soluble chlorophyll-binding (WSCP) complexes, in order to study system-bath coupling and energy transfer pathways. Site-selective techniques, e.g., hole burning (HB) and fluorescence line narrowing, are utilized to overcome static disorder and reveal details on homogeneous broadening. In addition, excitonic calculations with non-Markovian lineshapes provide information on electronic structure and exciton dynamics. A new lognormal functional form of the spectral density is recommended which appropriately defines electron-phonon parameters, i.e., Huang-Rhys factor and reorganization energy. Absorbance and fluorescence spectral shifts and HB spectra reveal that samples of FMO may contain a subpopulation of destabilized proteins with modified HB efficiencies. Simulations of spectra corresponding to intact proteins indicate that the entire trimer has to be taken into account in order to properly describe fluorescence and HB spectra. The redshifted fluorescence spectrum of WSCP is described by uncorrelated energy transfer as opposed to previous models of excited state protein relaxation. Also, based on nonconservative HB spectra measured for WSCP, a mechanism of electron transfer between chlorophylls and aromatic amino acids is proposed.
Keywords: Photosynthesis; Spectral Hole Burning; Fenna-Matthews-Olson Complex